Bliskość pomiędzy językami słowiańskimi a integracja uchodźców z Ukrainy w Polsce - Saturno, Jacopo (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2023)
The paper is devoted to the specificities of the acquisition of L2 Polish by speakers of a closely related language (East Slavic one), with specific regard to the language-teaching consequences of said proximity. After an introduction to the current historical and sociolinguistic context of the East Slavic immigration to Poland, the data presents the concept of “intercomprehension”. Its impact on the acquisition of L2 Polish is illustrated by the use of empirical data collected by the author’s research team. The article is concluded by means of a reflection on the value of multilingualism in the school system and the skills required of Polish teachers in the present historical contingencies. It is argued in particular that due to the great number of Ukrainian pupils enrolled in the Polish schools, it is advisable for Polish school teachers to have at least some knowledge of the native languages of these pupils, with the primary goal of improving communication in stressful situations and adequately interpret and correct their errors in L2 Polish.